Optimisasi Algoritma Pemrograman Untuk Pengolahan Data Besar - Siti Izzati Sarah; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2024)
Big data processing has become an important aspect of computer science and various industries in the digital age. Efficient and timely programming algorithms play a central role in addressing the challenges presented by big data. This journal focuses on various optimization methods and techniques that can be applied in the development of programming algorithms for processing big data. Supporting and relevant references are used to illustrate the concepts and techniques presented in this paper. Discussions include parallel methods, data compression, indexing, divide and conquer strategies, and greedy algorithm approaches. Case studies on the implementation of fast sorting algorithms in the context of big data processing are also presented. The understanding and application of these optimization methods are important in maximizing the efficiency and performance of programming algorithms in dealing with big data, and they play a key role in the development of relevant information technology solutions.